2015
DOI: 10.1371/journal.pone.0116513
|View full text |Cite
|
Sign up to set email alerts
|

Determinants for Achieving the LDL-C Target of Lipid Control for Secondary Prevention of Cardiovascular Events in Taiwan

Abstract: BackgroundEpidemiological and clinical studies have clearly established the link between low-density lipoprotein cholesterol (LDL-C) and atherosclerosis-related cardiovascular consequences. Although it has been a common practice for physicians to prescribe lipid-lowering therapy for patients with dyslipidemia, the achievement rate is still not satisfied in Taiwan. Therefore, the determinants for achieving the LDL-C target needed to be clarified for better healthcare of the patients with dyslipidemia.MethodThis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
35
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(36 citation statements)
references
References 38 publications
(31 reference statements)
0
35
1
Order By: Relevance
“…Despite these disadvantages, our real-world nationwide data remains valuable for answering uncertain questions and guiding experimental studies. We wish this could help to improve the lower target-achieved rate in IS patients in the future (9,10).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite these disadvantages, our real-world nationwide data remains valuable for answering uncertain questions and guiding experimental studies. We wish this could help to improve the lower target-achieved rate in IS patients in the future (9,10).…”
Section: Discussionmentioning
confidence: 99%
“…However, the target achievement of LLT in stroke is not as good as in coronary artery disease (CAD) patients (9,10). Fewer trials have focused on the secondary preventive effects of LLT in stroke patients (11)(12)(13), and most supporting data comes from post hoc analyses or meta-analysis of studies that initially enrolled CAD patients (2, 14 -16).…”
mentioning
confidence: 99%
“…The results showed that senior patients aged 60 years and older were more likely to achieve treatment goals in both MR and HR groups. Likewise, in a recently published Taiwanese study, older Chinese patients were more likely to attain LDL‐C treatment goal for secondary prevention of cardiovascular disease . It alluded to the patients' perceived risk of further complications with rising age, prompting them to be proactive in taking measures to attain treatment control …”
Section: Discussionmentioning
confidence: 99%
“…LI and MI levels of LLT were used to manage over 90% of the three risk groups (Table ). The Taiwanese study also showed that most patients were on regimens of very low to low equipotent doses of statins …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation